Predicting Malaysian corporate spin-offs using wealth transfer and debt risk reallocation - Yoon, Teik Wei (2020)
Despite the popularity and increase in complexity of spin-offs in Malaysia and the recent development in the investor protection regulations, regulators, corporations, and stakeholders alike still relied on generalized spin-off wealth effect measurements that are oblivious to market climate factors, and they are an imperfect gauge for predicting spin- off potentials. This study measures the shareholders' wealth effect of spin-offs announcements in Malaysia under different corporate environments and tests the wealth transfer hypothesis to explain the measurements. Market Model analysis results show that spin-offs in Malaysia generally result in statistically significant positive cumulative average abnormal returns and further analysis via sub-sampling saw normal spin-offs achieve more while crisis spin-offs achieved adversely. Spin-off potential to gain and to lose were significantly higher than generalized average value. Multivariate analysis using financial distress inducing variables: collateral, leverage, maturity, and security show evidence of wealth transfer through the loss of collateral, short-term debts and interest-bearing-secured debts impact are more prevailing. The wealth transfer hypothesis is even valid for debt without covenants during adverse financial market conditions where creditors’ have heightened risk sensitivity. Market players can expect higher returns during non-crisis spin-offs, project higher spin-off potential to gain, vice- versa, and predict shareholders’ gain via creditor’s risk reallocation. Regulators on the other hand, must attend to the regulatory weakness in preventing non-covenant backed creditors’ wealth appropriation.